Synthetic Speech Used to Treat Language Delay - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1996)
Deficits in recognition and processing of rapidly successive phonetic elements of speech in language-learning impaired (LLI) children, aged 5 to 10 years, treated at Rutgers University, Newark, NJ, and University of California, San Francisco, were improved by listening to acoustically modified synthetic speech and by daily training with computer "games" designed to modify temporal processing and phoneme perception.